Оrganizational and legal procedures for protection of a commercial secret of business subsidiary - Zaitseva-Kalaur, Inna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The scientific article is devoted to the study of legal and organizational aspects of the protection of commercial secrets;the main stages of the process of assigning information to commercial secrets are highlighted; modern, effective system of information protection that is commercially valuable for a business entity is analysed.